До питання про варварські релігійні впливи у Херсонесі Таврійському - Шевченко, Т.М. (Археологія, 2005)
У статті розглянуто історію вивчення верховного божества Херсонеса. Проаналізовано основні підходи до дослідження, зокрема ідею про варварські запозичення в релігійних уявленнях. В статье рассмотрена история изучения верховного культа Херсонеса Таврического. Прослежено развитие теории варварских влияний в сфере религии. Учитывая археологические, эпиграфические и нумизматические сведения о культе Партенос, а также взаимосвязи дорической колонии с местным населением, верховный культ Херсонеса не следует рассматривать с точки зрения теории варваризации. При изучении херсонесской религии нужно принимать во внимание дорический консерватизм и особенности исторического развития полиса. The article deals with the backgrounds of study of the main cult of the Tauric Chersonesos. The development of theory of the barbaric influence on religion is traced. Taking into consideration the archaeological, epigraphic and numismatic evidence of Parthenos’ cult, as well as the relationship of the Doric colony with barbarians, the supreme cult of Chersonesos should not be viewed with relation to the «barbarization» theory. The Doric conservatism and the peculiarities of the polis’ religion should be taken into account when studying the religion of Chersonesos.